One-step solution synthesis of a two-dimensional semiconducting covalent organometallic nanosheet via the condensation of boronic acid. Issue 50 (17th September 2019) - Wang, Qijun; Yan, Jiahao; Xiao, Mingchao; Manoj, Devaraj; Zhong, Cheng; Lv, Qiying; Yang, Lite; Wu, Liangmei; Wang, Zhuoping; Bao, Lihong; Gao, Hongjun; Xiao, Fei; et al.
Abstract : A 2D covalent organometallic nanosheet (COMS-Co) was synthesized through the one-step conjunction of sandwich coordinate motif with covalent heterocyclic linkage via the condensation of boronic acid, and it showed promising semiconducting properties. Abstract : In this work, a 2D covalent organometallic nanosheet (COMS) was designed and successfully synthesized through the one-step conjunction of a terpyridine–metal–terpyridine (TMT) sandwich coordinate motif with borate ester covalent heterocyclic (B3 O3 ) linkage via the condensation of boronic acid. The obtained 2D COMS with a cobalt coordination center (2D COMS-Co) showed promising p-type semiconducting properties.